Eosinophilic esophagitis - Carr, Stuart (BioMed Central, 2011)
Eosinophilic esophagitis (EoE) is an atopic condition of the esophagus that has become increasingly recognized over the last decade. Diagnosis of the disorder is dependent on the patient’s clinical manifestations and histologic findings on esophageal mucosal biopsies. Patients with eosinophilic esophagitis should be referred to both an allergist and gastroenterologist for optimal management, which may include dietary modifications, pharmacologic agents such as corticosteroids, leukotriene modifiers and biologics as well as mechanical dilatation of the esophagus. The epidemiology, pathophysiology, diagnosis, treatment, and prognosis of EoE are discussed in this review.